Analisis Struktur Naratif Geguritan Bhiksuni - Ni Wayan Yuni Astuti; Ida Bagus Putu Eka Suadnyana (Pramana: Jurnal Hasil Penelitian, 2022)
One of the literary works that have very high educational values and is considered as something that can provide guidance or guidance in life is Geguritan. Geguritan Bhiksuni is one of the evidences for the Balinese people and as a mirror of traditional Balinese culture and the educational values contained in it. The values contained in it can be used as guidelines to be understood and internalized properly. The purpose of this study was to determinethe values of Hindu religious education contained in geguritan bhiksuni. This research is in the form of a descriptive qualitative design by examining the text. Data were collected using library techniques and critical reading techniques. After the data is collected then the data is analyzed through three stages, namely data reduction, and data presentation. based on the results of the study it was found that the value of Hindu religious education in the geguritan bhiksuni was ethical values and tawwa values.